Probabilistic Finite Element Analysis of Temperature-Dependent Corrosion in Oil and Gas Pipelines - Nrior, Million Matthew; Nitonye, Samson; Adumene, Sidum; Orji, Charles Ugochukwu (PT. Teknologi Futuristik Indonesia, 2026)
Marine pipeline systems are continually exposed to operating conditions that accelerate internal corrosion, posing risks to flow assurance and structural integrity. This study applies finite element modelling to evaluate the influence of operating temperature on corrosion progression and pipeline performance. The study addressed gaps in temperature-based corrosion propagation in a pipeline using ANSYS Design Modeler, meshing, and exporting for flow-corrosion modelling in ANSYS Fluent. A one-way coupling was established between Fluent and ANSYS Mechanical to assess the mechanical response under operating conditions. The base case at 62 °C showed a corrosion rate of 6.0 mm/year. To investigate the role of temperature, simulations were conducted at 30 °C, 50 °C, 62 °C, and 70 °C, representing the typical temperature range of Niger Delta fluid systems. Results indicate that lower temperatures significantly increase corrosion rates, leading to pronounced wall thinning and elevated stress concentrations. Conversely, higher temperatures reduce corrosion intensity by promoting the formation of protective corrosion films. However, localized stress elevations at higher temperatures were also observed, which may be attributed to combined thermal expansion effects and residual corrosion-induced weakening. This demonstrates a non-linear interaction between temperature, corrosion progression, and stress response. The study recommends maintaining sufficiently high fluid temperatures to mitigate corrosion. Further studies are needed to define the temperature range where corrosion behaves linearly, to support optimal design and operation while preventing conditions that could impair system performance and flow assurance. The result provides technical insight for the development of an integrity management strategy for optimum pipeline safety.